Characterization of the Nonlinear Susceptibility of Monolayer MoS2 using Second- and Third-Harmonic Generation Microscopy - Woodward,RI; Murray,RT; Phelan,CF; de,Oliveira REP; Li,S; Eda,G; de,Matos CJS (2016)
Second- and third-harmonic generation microscopy of monolayer MoS2 is reported for imaging and characterization of the material's nonlinearity. A telecommunication wavelength pump is used, revealing the material's promise for use in nonlinear optical devices.